El libramiento norponiente de San Luis Potosí: proceso de rururbanización, resistencia, intermediación y valorización de tierras - Guzmán Chávez, Mauricio Genet; Madrigal González, David; Ávila Cervantes , Juan Manuel (El Colegio de México A.C., 2022)
The urbanization processes of the metropolitan peripheries have been a recurring topic of discussion within the various disciplines of the social sciences. In this article, we offer an ethnographic analysis –case study– of the conflict that was triggered by the construction of the north-west bypass in the metropolitan area of San Luis Potosí, between 2012 and 2016 and that continues to the present. The bypasses “engulf” towns and rural settlements, the rhythm of this process depends on the forms of resistance and organization. Likewise, the forms of cooptation and intermediarism that emerge are essential to understand the new key to the disputes over the local reconfiguration of rural space.